643 Autopsy review of chimeric-antigen receptor T cell therapy: a single institution experience. (9th November 2020) - Kwon, KiBeom; Woolston, David; Hirayama, Alexandre; Green, Damian; Maloney, David; Turtle, Cameron; Yeung, Cecilia
Abstract : Background: Our institution has treated over 300 patients with chimeric antigen receptor (CAR) T-cell immunotherapy (CAR T-cell therapy) since 2013. Phase I and II trials were primarily based on heavily treated patients with B cell acute lymphoblastic leukemia (B-ALL), aggressive diffuse large B cell lymphoma (DLBCL), and multiple myeloma (MM) who had failed multiple lines of prior chemotherapy and/or hematopoietic stem cell transplantation (HSCT). In these relapsed and/or refractory patients, CAR-T therapy resulted in complete remission in 93% of B-ALL, 60% of DLBCL, and 80% of MM. Our Pathology Group at Fred Hutch have reviewed and diagnosed various patients with interesting relapse or complications as a result of CAR T-cell therapy. Here we present a retrospective review of autopsies from CAR T-cell therapy. Methods: A search for all autopsies conducted on patients from Seattle Cancer Care Alliance/University of Washington Medical Center was performed using the keywords 'CAR T' and 'Chimeric-antigen'. Our inclusion criteria were patients treated with CAR T-cell therapy. Pathology and clinical records were reviewed for cause of death, disease and treatment timelines, microbiology data, cytokine levels, other pathology biopsies, and pertinent laboratory values. Histologic tissues were reviewed. Results: Twelve autopsies were performed since 2013. Patient characteristics and causes of death are summarized in table 1. The most common cause of death was due to infectious causes (n=6). Two patients (Patients 10 and 11) had cardiovascular related deaths. Six patients (Patients 1, 2, 6, 7, 10, 12) suffered from CRS in their post-infusion course, four of whom (Patients 1, 2, 7, 10) had CRS directly attributed as the cause of death. CRS was further complicated by immune effector cell-associated neurotoxicity syndrome (ICANS) in 5 patients (Patients 1, 5, 6, 7, and 12). CRS with ICANS was the second most common cause of death in patients treated with CAR T-cells. Three patients (Patients 1, 4, 9) had progression of disease that attributed to cause of death. Conclusions: CAR T-cell therapy is a highly effective treatment even for patients who have relapsed and/or refractory disease. Post-therapy complications range in severity and may be fatal in rare instances as in the patients summarized in this study. Infection, CRS with ICANS are the most common causes of death in our single institution study. Ethics Approval: The study was approved by Fred Hutchinson Cancer Research Center's Institutional Review Board, approval number 1837 Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal.